Diseño y fabricación de microinductor planar para microválvula activa para el tratamiento de glaucoma utilizando tecnología MEMS - Pérez, M. C. (2011)
This paper presents the modeling, design and characterization of planar microinductor, to be used in telemetry systems that supply energy to miniaturized implants. First, a model for the electrical characteristics of planar coils will be discussed. Parasitic electrical effects that may become important at AC-frequencies of several MHz are evaluated. The fabrication process and electrical characterization of planar microcoils will be described. Different configurations of planar microinductor were made with the use of micromachining technologies such as thin film deposition, standard photolithography processes and electroplating. With this technology small coils are relatively easy to fabricate reproducibly. The parameters and performance of fabricated inductor will be evaluated by electrical measurements. Measurements show a good agreement between calculated and measured values.